Analisis Dan Perancangan Sistem Informasi Layanan Penerimaan Tamu Pada Sekretariat Daerah Kantor Gubernur Provinsi Jambi - Fariza, Adha; Mulyono, Herry (Jurnal Manajemen Sistem Informasi, 2020)
At this time, the process that occurs in the Secretariat of the Provincial Office of the Governor of Jambi 1) Prospective visitors or guests must find the destination Bureau, while the Governor's office has many (nine (nine)) Bureaus. 2) Prospective visitors or must order a guest book / send a request letter to the Administration (TU). 3) The number of Administration (TU) in the Gubernur Office, in each Bureau has one Administration (TU). 4) Guest books are separated from each Administration (TU). 5) Prospective visitors or guests who do not know that guests will be met. The purpose of this study is to analyze and design an information system for reception services to help the visit process and make it easier to register guests. In the analysis and design of the system researchers used the method of object-oriented approach that is UML while for the design of the display using a prototype. The results of this study are information systems for reception services at the Regional Secretariat in the Office of the Governor of Jambi Province that has the feature to fill in guest data online and find out whether there are officials who want to be met. This feature can help people / guests who want to visit more easily make an appointment.